(untitled) (Eastern Journal of Medical Sciences, 2020)
Background: Preeclampsia is a common medical problem associated with pregnancy with substantial risk to the mother and fetus. Abnormal lipid metabolism seems important in the pathogenesis of pregnancy-induced hypertension. Objective: The objective was to study the alteration of various lipids in pregnancies complicated by hypertensive disorders. Materials and Methods: This prospective study was conducted among 150 pregnant women in the department of obstetrics and gynecology, from September 2009 to May 2011. The subjects were divided into two groups of normotensive women and women with complicated pregnancy by hypertensive disorder with 75 patients each. Serum lipid profile including total cholesterol, triglyceride (TG), low-density lipoprotein (LDL), and high-density lipoprotein (HDL) was determined and compared between the two groups. The data were analyzed using the Chi-square test and analysis of variance test. p<0.05 was considered statistically significant. Results: The mean TG level in the normotensive women was 121.5±25.0, while in the preeclamptic women were 311.4±79.5 (p<0.001). The mean cholesterol level was 181.7±27.8 in the normotensive and 259.4±40.6 in the hypertensive arm (p<0.001). Mean LDL was 122.6±24.6 in the normotensive group whereas 255.3±41.9 in the hypertensive pregnant women (p<0.001). HDL was 49.4±5.6 in the normotensive and 49.7±5.5 in the hypertensive arm (p=0.69). Conclusion: The endothelial dysfunction in preeclampsia could be due to an altered lipid profile. This association of hyperlipidemia may be significant in understanding the pathogenesis of preeclampsia and may help in developing strategies for early diagnosis and prevention of preeclampsia.